PERAN TOKOH AGAMA DALAM KETAHANAN SOSIAL: TINJAUAN LITERATUR DAN ANALISIS KONSEP - Urifah, Dewi; Hasanah, Niswatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to identify and develop a conceptual model regarding the contributions of religious leaders to social resilience by integrating findings from both theoretical and empirical literature. The results of this study are expected to enrich the academic literature and provide practical guidance for policymakers and practitioners in designing strategies to enhance social resilience involving religious leaders. The research methodology employs a literature review and concept analysis approach, beginning with a review of relevant theoretical and empirical sources, followed by evaluation and categorization of the literature to identify key themes and relationships between concepts. The conceptual analysis aims to construct a comprehensive model illustrating the role of religious leaders in conflict mediation, social change advocacy, emotional support, and social aid organization. The study finds that religious leaders play a central role in strengthening social networks and community solidarity, which supports social resilience. The findings indicate that religious leaders are effective as conflict mediators, social change advocates, emotional support providers, and social aid organizers. However, there is a gap in the literature concerning the application of theory in practical contexts. This research makes a significant contribution by developing a more inclusive and applicable conceptual model, offering a framework for further research and practice. The findings have the potential to influence public policy by highlighting the importance of involving religious leaders in social resilience strategies and providing guidance for the implementation of the model in various contexts.